Spatial Distribution of Butterfly (Lepidoptera: Papilionoidea) in Taman Negara Johor Endau Rompin (Peta), Mersing, Johor, Malaysia - Ismail, Norradihah; Mohamed, Maryati; Phon, Chooi Khim; Tokiman, Lili (Journal of Science and Technology, 2018)
Being the largest protected area and an old tropical rainforest in the southern Peninsular Malaysia, Taman Negara Johor Endau Rompin (TNJER) is home for diverse flora and fauna. The present biodiversity and ecology of forest ecosystem need to be understood to facilitate park management and conservation effort. Butterfly is useful for ecological evaluation of terrestrial landscapes and management of natural areas due to their sensitivity in responding toward environmental variations. The samplings were conducted manually using aerial net and trapping using fruit baits along two of 1 km transects in the eastern part of TNJER (Nature Education and Research Centre and Kuala Jasin) from April 2014 to July 2015. A total of 131 species comprising 491 individuals from five families were recorded. This study had also successfully added 27 new records for TNJER. The most dominant species are Graphium sarpedon, Bassarona teuta and Zizeeria karsandra. The value of Shannon diversity and species evenness indices were 4.123 and 0.471 respectively. This indicated the high diversity of butterfly in the park. The curve of species accumulation graph was still increasing by the end of this study. Using Inventory Completeness Index, this sampling effort had covered only 51.15%. Using non-parametric estimator namely Chao1 suggested an estimated additional 87 species are expected to be found if the sampling continued. The chances of finding additional species are considered high due to high number of singletons (48.9%) and doubletons (16.8%) species recorded in this study. More comprehensive diversity and ecological studies are crucial to facilitate in comparing species from newer tropical forest of Borneo and other parts of Southeast Asia and to gauge in term of biogeography and conservation aspects. This study had produced a comprehensive checklist of butterfly in TNJER, comprising of 349 species, and it could be a reference point to understand the overall diversity of butterfly in Johor.